A Paleolithic diet lowers resistant starch intake but does not affect serum trimethylamine-N-oxide concentrations in healthy women. Issue 3 (17th December 2018) - Genoni, Angela; Lo, Johnny; Lyons-Wall, Philippa; Boyce, Mary C.; Christophersen, Claus T.; Bird, Anthony; Devine, Amanda
Abstract: The Paleolithic diet excludes two major sources of fibre, grains and legumes. However, it is not known whether this results in changes to resistant starch (RS) consumption. Serum trimethylamine- N -oxide (TMAO) is produced mainly from colonic fermentation and hepatic conversion of animal protein and is implicated in CVD, but changes in RS intake may alter concentrations. We aimed to determine whether intake of RS and serum concentrations of TMAO varied in response to either the Paleolithic or the Australian Guide to Healthy Eating (AGHE) diets and whether this was related to changes in food group consumption. A total of thirty-nine women (mean age 47 (sd 13) years, BMI 27 (sd 4) kg/m 2 ) were randomised to AGHE ( n 17) or Paleolithic diets ( n 22) for 4 weeks. Serum TMAO concentrations were measured using liquid chromatography–MS; food groups, fibre and RS intake were estimated from weighed food records. The change in TMAO concentrations between groups (Paleolithic 3·39 μm v . AGHE 1·19 μm, P = 0·654) did not reach significance despite greater red meat and egg consumption in the Paleolithic group (0·65 serves/d; 95 % CI 0·2, 1·1; P <0·01, and 0·22 serves/d; 95 % CI 0·1, 0·4, P <0·05, respectively). RS intake was significantly lower on the Paleolithic diet ( P <0·01) and was not associated with TMAO concentrations. However, the limited data for RS and the small sample size may have influenced these findings. While there were no significant changes in TMAO concentrations, increased meat consumption and reduced RS intake warrant further research to examine the markers of gastrointestinal health of Paleolithic diet followers and to update Australian food databases to include additional fibre components.